The Correlation between Quality of Work Life and Job Satisfaction Among Nurses at RSU Dadi Keluarga Purwokerto Hospital - Pambajeng Utami; Tri Sumarni; Pramesti Dewi (LPPM Universitas Harapan Bangsa, 2024)
Job satisfaction is an important focus in healthcare services as it can affect patient satisfaction levels. Nurses feel satisfied when they experience good quality of work life, as job satisfaction itself is influenced by the level of quality of work life they undergo. The purpose of this study was to identify the relationship between quality of work life and job satisfaction levels at Dadi Keluarga Purwokerto Hospital. This research was conducted using quantitative methods and a cross-sectional approach. All 44 nurses at the hospital were made research subjects using total sampling technique. The job satisfaction measurement tool used was the Minnesota Satisfaction Questionnaire (MSQ), while quality of work life was measured through a Quality of Work Life questionnaire. The results showed that 77.2% of nurses had moderate levels of job satisfaction, while 81.8% had fairly good quality of work life. Spearman Rank analysis resulting in a p-value of 0.00 (<0.05) meant that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted, with a correlation coefficient of 0.588 indicating a strong relationship between quality of work life and job satisfaction among nurses at Dadi Keluarga Purwokerto Hospital. This study advises nurses to further improve their quality of work life to determine strategies to enhance job satisfaction. Future researchers are recommended to examine other aspects such as commitment, work stress, work culture in relation to nurses' quality of work life and job satisfaction. Dadi Keluarga Purwokerto Hospital is also advised to establish a supportive work environment to achieve good quality of work life and job satisfaction.